Geostatistical Mapping of Groundwater Salinity and Seawater Intrusion in Coastal Aquifers of Jember Regency Using Physicochemical Parameters and Seawater Fraction - Mujib, Muhammad Asyroful; Astutik, Sri; Apriyanto, Bejo; Muhammad, Ikhlas Nur; Fitra, Audina Anugra (Geomedia Majalah Ilmiah dan Informasi Kegeografian, 2024)
Seawater intrusion significantly impacts groundwater quality in coastal areas, presenting a critical challenge for sustainable water resource management. This study aimed to map groundwater salinity in the southern coastal region of Jember Regency by employing simple physicochemical parameters, including Electrical Conductivity (EC), Total Dissolved Solids (TDS), and seawater fraction (fsea), which was determined using chloride (Cl-) concentrations. Fieldwork was conducted at 211 well sites across ten villages, and the sea-freshwater interface was analyzed using the Ghyben-Herzberg principle. Geostatistical analysis using Ordinary Kriging was applied to spatially map the salinity parameters. Results indicated that 83% of groundwater samples were classified as fresh, 16% as slightly saline, and 1% as moderately saline. Areas near Payangan and Watu Ulo Beaches exhibited higher seawater fractions, with fsea values up to 23%, indicating significant seawater mixing. These findings underscore the need for targeted groundwater management strategies to mitigate seawater intrusion in this region